DRAGON BOY - King-Smith, Dick; Walters, Jessica (United Kingdom : Sweet Cherry Publishing Limited, 2021)
Montagu Bunsen-Burner is on a diet. Concerned for his dragon digestion, his wife Albertina has taken humans off the menu. So when Montagu meets an orphaned boy in Sherwood Forest, he doesn't barbecue him. He adopts him. Little John proves useful with his knowledge of herbs and cooking, but his cleverness in finally hatching one of Albertina's eggs is what truly secures his place in the family. With his wolf Bart beside him, John bravely faces danger from animals, outlaws and fire. And as he grows, so does the legend of the dragon boy.
Keywords: Children's stories, English; Adoption -- Juvenile fiction; Dragons -- Juvenile fiction